Decreased Irradiance and Nutrient Enrichment Mitigate the Negative Effect of Ocean Warming on Growth and Biochemical Compositions of a Canopy-Forming Marine Macroalga - Harshna Charan; Eri Inomata; Hikaru Endo; Yoichi Sato; Yutaka Okumura; Masakazu N. Aoki (Journal of Marine Science and Engineering, 2022)
Heatwaves under global warming have negative impacts on ecosystem primary producers. This warming effect may be synergized or antagonized by local environments such as light and nutrient availability. However, little is known about the interactive effects of warming, irradiance, and nutrients on physiology of marine macroalgae, which are dominant in coastal ecosystems. The present study examined the combined effects of warming (23 and 26 °C), irradiance (30 and 150 µmol photon m−2 s−1), and nutrients (enriched and non-enriched) on specific growth rate (SGR) and biochemical compositions of the canopy-forming marine macroalga Sargassum fusiforme. The negative effect of warming on SGR and ratio of chlorophyll (Chl) c to Chl a was antagonized by decreased irradiance. Moreover, the negative effect of temperature elevation on carbon content was antagonized by nutrient enrichment. These results suggest that the effect of warming on the growth and carbon accumulation of this species can be mitigated by decreased irradiance and nutrient enrichment.